Exploring avocado consumption and health: a scoping review and evidence map - Fleming, Stephen A.; Paul, Tristen L.; Fleming, Rachel A. F.; Ventura, Alison K.; McCrory, Megan A.; Whisner, Corrie M.; Spagnuolo, Paul A.; Dye, Louise; Kraft, Jana; Ford, Nikki A. (Frontiers in Nutrition, 2025)
ObjectiveThis scoping review evaluates the breadth of research on avocado intake and health, considering all populations and health outcomes (registered on Open Science Foundation at https://osf.io/nq5hk).DesignAny human intervention or observational study where effects could be isolated to consumption of avocado were included. A systematic literature search through April 2024 was conducted (PubMed, Web of Science, Scopus, and CENTRAL) and supplemented by backwards citation screening. Dual screening, data extraction, and conflict resolution were performed by three reviewers and an interactive evidence map was created.ResultsAfter deduplication, 8,823 unique records were retrieved; 58 articles met inclusion criteria, comprising 45 unique studies (28 interventions, 17 observational studies). Studies were largely conducted in the United States or Latin America and generally included adults, with overweight/obesity, frequently with elevated lipid concentrations. Interventions assessed the impact of diets enriched in monounsaturated fatty acids, diets higher/lower in carbohydrates, or in free-feeding conditions. Larger amounts of avocados were used in interventions than commonly consumed in observational studies (60–300 vs. 0–10 g/d, respectively). Blood lipids, nutrient bioavailability, cardiovascular risk, glycemia, and anthropometric variables were the most common outcomes reported across all studies.ConclusionFuture recommendations for novel research include the study of: European, Asian, adolescent or younger, and senior populations; dose–response designs and longer length interventions; dietary compensation; and the need for greater replication. The results have been made public and freely available, and a visual, interactive map was created to aid in science translation. This evidence map should enable future meta-analyses, enhance communication and transparency in avocado research, and serve as a resource for policy guidance.